THE METRICS OF FOLK SONG: A COMPARATIVE STUDY OF TEXT-SETTING IN SPANISH AND ENGLISH - Rodríguez-Vázquez, Rosalía (Rhythmica. Revista Española de Métrica Comparada, 2014)
THE METRICS OF FOLK SONG: A COMPARATIVE STUDY OF TEXT-SETTING IN SPANISH AND ENGLISH